The Impact of TikTok Social Media on Communication Patterns: A Case Study of Generation Z Students at Universitas ‘Aisyiyah Yogyakarta and Their Parents - Alifiya, Diah Ayu; Kusumo, Herlambang Jati (The Eastasouth Journal of Social Science and Humanities, 2025)
This study aims to determine the effect of using the social media platform TikTok on the communication patterns of Generation Z students with their parents at Universitas ‘Aisyiyah Yogyakarta. The research background arises from the increasing intensity of TikTok use among teenagers and students, which may affect family interaction. This study used a quantitative descriptive method with data collected through questionnaires from 100 active students. The Pearson Product Moment correlation test showed a coefficient value of 0.749, indicating a strong and positive relationship between TikTok use and communication patterns. Meanwhile, the simple linear regression test showed a determination coefficient (R²) of 0.561, meaning TikTok use contributes 56.1% to changes in communication patterns between students and their parents. The study concludes that the higher the intensity of TikTok use, the greater the change in communication patterns between Generation Z students and their parents.